2000
DOI: 10.1542/peds.106.5.e65
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Injuries by Elastic Cords in Children

Abstract: ABSTRACT. Background. Elastic cords hitting the eyeball as high-speed projectiles can severely damage ocular structures and can produce permanent visual function impairment.Objectives. To evaluate the frequency, mechanics, and severity of eye injuries caused by elastic cords in children to adopt the most appropriate preventive measures.Methods. A retrospective medical records review of hospital admissions secondary to ocular trauma between 1991 and 1997 in a pediatric ophthalmology unit at an urban tertiary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In relation to closed eye injuries, similar to the previous studies, our study also showed that closed eye injuries caused by blunt objects, had a better final visual outcome. This compared to open eye injuries cause by similar objects, with only 6.1-20.8% of closed eye injuries caused by blunt objects had a final vision of worse than 0.7 (28)(29)(30). A common example of closed eye injuries caused by blunt objects seen in airbag accidents which is usually limited to zone I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to closed eye injuries, similar to the previous studies, our study also showed that closed eye injuries caused by blunt objects, had a better final visual outcome. This compared to open eye injuries cause by similar objects, with only 6.1-20.8% of closed eye injuries caused by blunt objects had a final vision of worse than 0.7 (28)(29)(30). A common example of closed eye injuries caused by blunt objects seen in airbag accidents which is usually limited to zone I.…”
Section: Discussionmentioning
confidence: 99%
“…Hyphema, traumatic iritis, iris sphincter rupture, angle recession, iridodialysis, iridodonesis, traumatic cataract, and phacodonesis are common findings in type A closed eye injuries that have extended to zone II. Temporary vision loss is reported in such injuries in 4.3-50% (28)(29)(30). It is important to remember that angle recession glaucoma is a common finding in type A closed eye injuries that have extended to zone II.…”
Section: Discussionmentioning
confidence: 99%
“…Gardening and do-it-yourself (DIY) activities have previously been highlighted as common causes of ocular injury, although the risks are often overlooked by those engaging in such activities, 31 and the dangers associated with misuse of bungee cords are widely known. 32 , 33 Each of these has the potential to cause serious ocular injury, but are easily preventable, have previously been highlighted in the medical press, yet continue to be reported in this pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…• Μια αυξανόµενη αιτία σοβαρού οφθαλµικού τραύµατος, θλαστικού (90%) ή διατιτραίνοντος (10%), αποτελεί η χρήση των <<χταποδιών>>, δηλαδή ελαστικών σχοινιών µε µεταλλικούς ή πλαστικούς γάντζους σε σχήµα S στην άκρη τους(Cruysberg et al 1995, Cooney et al 1997, Chorich et al 1998, Da Pozzo et al 2000, Aldave et al 2001, Brouzas et al 2002, Viestenz et al 2002. Σε µελέτη των οφθαλµικών τραυµάτων από ''χταπόδι'' στην Αθήνα(Brouzas et al 2002), βρέθηκε ότι αποτελούν το 0.1% των οφθαλµικών τραυµάτων που προσέρχονται στο τµήµα επειγόντων περιστατικών, µε το 85.7% να αφορά σε άντρες και το 14.3% σε γυναίκες.…”
unclassified